Integracja w systemie oświaty w Izraelu i jej wpływ na rozwarstwienie społeczne w zmieniającym się świecie - Franco, Manor Sali (Studia Edukacyjne, 2020)
Among the phenomena that characterize modern society it is possible to note the appearance of complex political, occupational, and sectorial systems of status and the weakening of the ‘class’ factor in its ideological meaning. The main result of this development was the steadily increasing conflictbetween, on the one hand, the trends of economic development and the new centers of power and, on the other hand, the mobility of new groups. All the groups competed among themselves over the additions of income, accessibility to economic resources, and positions of influencein the government system as well as over the creation of autonomous frameworks. An important part in these sectorial formations is related to the positioning of education in the entire stratifiedsystem. The statement that the extension of education has not resulted in the reduction of social gaps in the professional field,especially between employees, is correct, yet conversely it did drive a process of change in the evaluation of different subjects and a change in the perception of education as a necessary state of specialization. This aspect constitutes an important factor in the processing of the stratifiedmap and in the formation of the class awareness. The education systems, which are the main organizations to inculcate education, can determine who is qualifiedand who is not qualifiedto filldifferent employment roles; they have become the main device for the achievement of social and economic status.